Proposta de metodologia para programação de serviços de um laboratório de calibração - (:unkn) unknown (Universidade Federal do Amazonas, 2010)
This paper presents a model for programming calibration services balance, applied to a calibration laboratory installed in the city of Manaus, in order to promote improvements in the management of productive capacity. The calibration of the measuring instrument is part of the metrological services that support enterprises that have a quality management system certificate. The proposed model, seeking to align itself with these management practices, adopts the structure of the mapping process organized phases input, processing and output. The research method used to construct the model is the literature in the areas of production management, service management and metrology. This consultation revealed some difficulties because the approach is relatively new in the service area. In this context, we surveyed the main features present in any operation targeting the sort of service calibration laboratory. The classification was established by combining the characteristics of the activities of front line service represented by the calibration scale and the rear of activities by managing the laboratory calibration, resulting in framing shop services based on the volume of customers served by day at the plant. In our case, the high degree of standardization and repeatability in this provision of the calibration scale, facilitated the use of tools of production planning and control, through the technical choice of sequencing of work orders and their proper calibration schedule, being pulled to the type selected. To evaluate this process were investigated performance measures consistent with the service sector, revealing management indicators applicable in the following the calibration of instruments. The results contributed to increasing productivity in services researched, reflecting the adoption of certain management practices based on principles of production system used in the manufacturing area.
Keywords: Programação da produção; Operações de serviços; Metrologia; Calibração; Production scheduling; Service operations; Metrology; Calibration; ENGENHARIAS: ENGENHARIA DE PRODUÇÃO